THU0377 Frequency of Antibodies for Diagnosis of Coeliac Disease in Patients with Connective Tissue Diseases and Inflammatory Arthopathies. (10th June 2014) - Rodriguez, G.R.; Zazzetti, F.; da Representaçao, S.; Lencina, M.V.; Barreira, J.C.
Abstract : Background: Coeliac disease (CD) is an autoimmune disease caused by exposure to gluten in genetically predisposed individuals. The detection of anti-transglutaminase IgA (tTG) and anti-endomysial (EMA) is used for screening of CD with sensitivity and specificity of 90% and 99%. The association between CD and connective tissue diseases (CTD) has been reported. Objectives: The objective was to describe the frequency of IgA tTG and EMA in patients with definite diagnosis of CTD and inflammatory arthropathies (IA). Methods: Patients ≥18 years with CTD and IA were included. Values of ≥20 for tTG (ELISA) and ≥10 for EMA (IIF) were considered positive. Medium were used for numeric variables and interquartile percentages for categorical variables. Confidence intervals were calculated for 95%. Results: Of 149 patients with various diagnoses included, 8 had at least one positive antibody (5.37% CI =1.75-8.99), 6 had both (4.03% CI =0.87-7, 18) and 2 had only tTG. Eight patients were diagnosed with CD and biopsy was performed in 4 (see table below). In this study 5.37% presented positive serology for CD. Positive antibodies were found in patients with Sjögren's syndrome, rheumatoid arthritis, psoriatic arthritis, polymyositis and lupus, as reported by other authors. Conclusions: According to our findings, it would be useful to perform a serological screening for CD in CTD, due to the overlap of autoimmune diseases, as well as in undifferentiated arthritis, to determine in those patients in whom the small bowel biopsy should be performed for definitive diagnosis. References: Gόmez JC, Selvaggio GS, Viola M, Pizarro B, La Motta G, de Barrio S et al. Prevalence of celiac disease in Argentina: screening of an adult population in the La Plata area. Am J Gastroenterol 2001; 96: 2700-4. Luft LM, Barr SG, Martin LO, Chan EK, Fritzler MJ. Autoantibodies to tissue transglutaminase in Sjögren's syndrome and related rheumatic diseases. J Rheumatol 2003; 30:2613-9. Koehne Vde B, Bahia M, Lanna CC, Pinto MR, Bambirra EA, Cunha AS. Prevalence of serological markers for celiac disease (IgA and IgG class antigliadin antibodies and IgA class antiendomysium antibodies) in patients with autoimmune rheumatologic diseases in Belo Horizonte, MG, Brazil.Arq Gastroenterol; 2010; 47:250-6. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2624